Multilayer Nanocarrier for the Codelivery of Interferons: A Promising Strategy for Biocompatible and Long-Acting Antiviral Treatment - Thelvia I. Ramos; Carlos A. Villacis-Aguirre; Felipe Sandoval Sandoval; Sarah Martin-Solano; Viana Manrique-Suárez; Hortensia Rodríguez; Leandro Santiago-Padilla; Alexis Debut; Carolina Gómez-Gaete; Marbel Torres Arias; Raquel Montesino; Emilio Lamazares; et al. (MDPI AG, 2024)
Background: Interferons (IFNs) are cytokines involved in the immune response with a synergistic regulatory effect on the immune response. They are therapeutics for various viral and proliferative conditions, with proven safety and efficacy. Their clinical application is challenging due to the molecules' size, degradation, and pharmacokinetics. We are working on new drug delivery systems that provide adequate therapeutic concentrations for these cytokines and prolong their half-life in the circulation, such as nanoformulations. Methods: Through nanoencapsulation using electrospray technology and biocompatible and biodegradable polymers, we are developing a controlled release system based on nanoparticles for viral infections of the respiratory tract. Results: We developed a controlled release system for viral respiratory tract infections. A prototype nanoparticle with a core was created, which hydrolyzed the polyvinylpyrrolidone (PVP) shell , releasing the active ingredients interferon-alpha (IFN-α) and interferon-gamma (IFN-γ). The chitosan (QS) core degraded slowly, with a controlled release of IFN-α. The primary and rapid effect of the interferon combination ensured an antiviral and immunoregulatory response from day one, induced by IFN-α and enhanced by IFN-γ. The multilayer design demonstrated an optimal toxicity profile. Conclusions: This formulation is an inhaled dry powder intended for the non-invasive intranasal route. The product does not require a cold chain and has the potential for self-administration in the face of emerging viral infections. This novel drug has applications in multiple infectious, oncological, and autoimmune conditions, and further development is proposed for its therapeutic potential. This prototype would ensure greater bioavailability, controlled release, fewer adverse effects, and robust biological action through the simultaneous action of both molecules.